2021
DOI: 10.3389/fpsyt.2021.654430
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Predictors of Health Care Workers Depression During the COVID-19 Pandemic: Health Facility-Based Study in Eastern Ethiopia

Abstract: Background: Depression of health care workers was related to work absences, resignations, and poor work performance, affecting the quality of patient care and the health care system. The Coronavirus disease pandemic has had an effect on the mental health of health care workers. Health care workers are facing challenges that can be stressful, overwhelming, and cause strong emotions, may put them at higher risk to develop depression. There is limited evidence that assesses health care workers' depression and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(56 reference statements)
3
6
1
Order By: Relevance
“…However, since COVID-19 was highly transmissible and was linked to high morbidity as well as potential death, it still represented a sustained psychological burden on HCWs (22). Overall, the results suggested that psychological problems were more prevalent in female HCWs compared with males and this was in line with previous studies conducted in China (8), Ethiopia (20), Italy (21), India (19) and Egypt (23). Studies have shown that females tend to perceive themselves as more likely to fall into stressful circumstances than males (24).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, since COVID-19 was highly transmissible and was linked to high morbidity as well as potential death, it still represented a sustained psychological burden on HCWs (22). Overall, the results suggested that psychological problems were more prevalent in female HCWs compared with males and this was in line with previous studies conducted in China (8), Ethiopia (20), Italy (21), India (19) and Egypt (23). Studies have shown that females tend to perceive themselves as more likely to fall into stressful circumstances than males (24).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the results suggested that psychological problems were more prevalent in female HCWs compared with males and this was in line with previous studies conducted in China ( 8 ), Ethiopia ( 20 ), Italy ( 21 ), India ( 19 ) and Egypt ( 23 ). Studies have shown that females tend to perceive themselves as more likely to fall into stressful circumstances than males ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study from Singapore found that non-medical HCWs reported more anxiety compared to medical HCWs ( 31 ). Of interest is a study from Ethiopia that found that HCWs who perceived themselves as being at risk if infected with COVID-19 were four times more likely to be depressed in comparison to their colleagues ( 32 ), which points to the relevance of various psychological variables and personal views related to the individual risk of COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses with chronic medical illness, children to take care of at home, and rotational shifts contributed to increasing stress experiences (Dechasa et al, 2021;Baye et al, 2020). In the face of the current pandemic, depressive symptoms were high among nurses' secondary to the mental effects and concerns about safety (GebreEyesus et al, 2021;Yadeta et al, 2021). The findings of the current study had described the context of stress, anxiety, depression, and burnout in the workplace that serve to provide recommendations for needed action.…”
Section: Relationship Of Nurses' Stress Anxiety and Depression To Bur...mentioning
confidence: 80%